Adaptation and Validation of the Subtle and Blatant Prejudice Scale in a Colombian Sample - Palacio, Jorge (2020)
The main objective of this study was to establish the psychometric properties for Colombia of the Subtle and Blatant Prejudice Scale of Pettigrew and Meertens (1995) which was adapted to Spanish by Rueda and Navas (1996). Venezuelan immigrants in Colombia are the target population. The sample comprised 1078 Barranquilla residents (Atlantic) who were selected intentionally, with an age range between 18 and 78 years old (M = 34.6 and SD= 13.4), of whom 49 % (n=523) were male. Outcomes show a Cronbach’s alpha (?) of .84 and an Omega (?) of .85 for the global scale. The Subtle Prejudice subscale displays ? = .74 and ? = .75, while the Blatant Prejudice subscale demonstrates ? = .78 and ? = .80. Confirmatory Factor Analysis confirms the underlying factorial structure, but item 17 changes factor and item 7 is eliminated, leaving a total of 19 items. Limitations are discussed.